'Man up': Medical students' perceptions of gender and learning in clinical practice: A qualitative study. Issue 2 (19th November 2019) - Samuriwo, Ray; Patel, Yasumati; Webb, Katie; Bullock, Alison
Abstract : Context: Gender‐related inequality and disparity hinders efforts to develop a medical workforce that facilitates universal access to safe, just and equitable health care. Little is known about how medical students perceive the impact of their gender on their learning in clinical practice. Our aim in this study was to address this gap, establishing students' perceptions of the impact of their gender on learning in the clinical context as part of the wider medical education community of practice. Methods: We undertook a qualitative study that simultaneously gathered data through narrative individual interviews and online case reports from male and female students (n = 31) from different academic cohorts with prior experience of clinical practice in a Russell Group University medical school in the UK. Interviews were transcribed and analysed thematically alongside case report data. Results and discussion: The participants revealed that there was a culture in clinical practice where their gender influenced how they were taught and supported by senior medical and surgical colleagues. Gender was also said to determine the clinical learning opportunities afforded to students, especially with regards to the care of patients of a different gender. The mentorship and support for learning provided to students in clinical practice was also said to be influenced by the medical student's gender. Conclusion: Our findings suggest that students undergo a gendered clinical apprenticeship within what are in effect gendered communities of practice with some distinct features. These findings underscore the imperative for further work to establish how medical students of all genders can be supported to fulfil their potential in clinical practice. Abstract : Exploring issues of gender, the authors report that medical students perceive clinical training to take place within gendered communities of practice that influence their experience learning in workplace environments.